Generating two-dimensional schematic diagrams of mechanical, electrical, and plumbing systems from three-dimensional building information models. (September 2016) - Matsubayashi, Michio; Watanabe, Shun
In this article, we propose a method of generating two-dimensional schematic diagrams from three-dimensional models of mechanical, electrical, and plumbing systems on computer-aided design software to represent this information in a more traditional, user-friendly format. It can be difficult to grasp the relationships between various mechanical, electrical, and plumbing elements in building information models because they are represented in a visually complex, three-dimensional manner. On the other hand, the relationships between building elements can be easily understood when using traditional schematic diagrams. First, the network of mechanical, electrical, and plumbing systems and a section view are extracted separately from three-dimensional models. Next, these extracted files are displayed as schematic diagrams on computer-aided design software. The expressions of traditional drawings were referenced to generate new diagrams. After schematic diagrams were created, they were evaluated by staff members in the facilities department of a university in Japan.